Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Matematika Siswa SD - Mahsup Mahsup; Abdillah Abdillah; Syafril Syafril (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  The purpose of this study is to analyze the use of the Problem Based Learning (PBL) learning model in learning can improve the learning outcomes of Mathematics for elementary school students. The research uses the meta-analysis method. Data collection was carried out by browsing electronic journals through google scholar and documentation studies in the library. Research data sources from 12 journals. Data analysis was carried out in a qualitative description. The results of the study show that the application of the Problem Based Learning model has a positive influence on improving student learning outcomes. This is marked by an increase in learning outcomes before and after the implementation of the Problem Based Learning modelAbstrak: Tujuan dari penelitian ini adalah untuk menganalisis penggunaan model pembelajaran Problem Based Learning (PBL) dalam pembelajaran dapat meningkatkan hasil belajar Matematika siswa SD. Penelitian menggunakan metode meta analisis. Pengumpulan data dilakukan dengan cara menelusuri jurnal elektronik melaluigoogle scholardan studi dokumentasi di perpustakaan. Sumber data penelitian dari 12 jurnal. Analisis data dilakukan secara deskripsi kualitatif. Hasil penelitian bahwa penerapan model Pembelajaran Problem Based Learning memiliki pengaruh yang positif dalam meningkatkan hasil belajar siswa. Hal itu ditandai dengan adanya peningkatan hasil belajar sebelum dan sesudah diterapkannya model pembelajaran Problem Based Learning